2016
DOI: 10.1136/jclinpath-2016-203696
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated PCR detection of KRAS mutations on pancreatic endoscopic ultrasound fine-needle aspirates

Abstract: This is the first study that applied the novel Idylla KRAS test to the clinical setting of pancreatic cancer. In particular, this system can be easily implemented in the routine assessment of pancreatic EUS-fine-needle aspiration-derived DNA samples to quickly provide information on KRAS mutational status to supplement cytological evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
5
15
0
Order By: Relevance
“…Nevertheless, rare EGFR and KRAS variants and mutations in other molecular targets are not detected by this fast diagnosis platform to date. In previous studies, Idylla did not detect double mutants (eg, KRASG12V and KRASQ61H mutant) but only reported the mutation with the smallest ΔCq per assay/cartridge 16. In our study, Idylla identified every KRAS and EGFR activating mutations including two samples with a double mutation ( EGFRG719X and EGFRS768I mutations in case #1; EGFRG719X and EGFRL861Q in case #9).…”
Section: Discussionsupporting
confidence: 43%
“…Nevertheless, rare EGFR and KRAS variants and mutations in other molecular targets are not detected by this fast diagnosis platform to date. In previous studies, Idylla did not detect double mutants (eg, KRASG12V and KRASQ61H mutant) but only reported the mutation with the smallest ΔCq per assay/cartridge 16. In our study, Idylla identified every KRAS and EGFR activating mutations including two samples with a double mutation ( EGFRG719X and EGFRS768I mutations in case #1; EGFRG719X and EGFRL861Q in case #9).…”
Section: Discussionsupporting
confidence: 43%
“…Our data showed that, when clinical decisions should be taken quickly and when saving time is a crucial issue, since days have been spent for an ‘invalid’ NGS result, Idylla can provide a solution. As a general rule, regardless of the sample type, we directly pipetted in the cartridge from 3 up to 10 µL of extracted DNA preparation 4. Indeed, in this study, Idylla ‘rescued’ a large portion of cases (20/25; 80%) whose preliminary assessment by NGS was unfeasible (figure 4).…”
Section: Discussionmentioning
confidence: 78%
“…Although this procedure had been designed by the manufacturer to process 5–10 µm FFPE tissue sections, we have previously shown that archival extracted DNA can directly be pipetted inside an EGFR Idylla cartridge 4. Cases with valid NGS results were tested by pipetting 3 µL (corresponding to 1/10th of the original DNA preparation from the sample).…”
Section: Methodsmentioning
confidence: 99%
“…The instrument is composed of a sample preparation module integrated with a combined PCR thermocycling and fluorescence detection module. All consumables required to perform sample preparation and RT-PCR detection are provided in a single disposable cartridge that is loaded into the Idylla system to enable the simultaneous detection of up to 30 molecular targets from a variety of solid and liquid sample types, including DNA preparations from routine cytological specimens 10. Closing of the cartridge after inserting the sample avoids cross-contamination.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, Biocartis developed an Idylla EGFR test prototype. Although, the Idylla tests were designed for use with formalin-fixed paraffin-embedded (FFPE) sections, the Idylla system can also process DNA preparations from cytological samples, as previously shown 10. The aim of the present study was to assess the Idylla EGFR test performance on lung cancer cytological specimens.…”
Section: Introductionmentioning
confidence: 98%